The impact of temperature on labor quality: Umpire accuracy in Major League Baseball - FESSELMEYER, Eric (Institutional Knowledge at Singapore Management University, 2021)
Using data from Major League Baseball, I compute an objective measure of the home plate umpire's work quality-the accuracy of his ball and strike calls during a game-and measure how it varies with temperature. I find that an increase in game-time temperature from between 70 and 80 degrees F to above 95 degrees F decreases an umpire's accuracy by a little less than a percentage point, which is a 5.5% increase in the pitch-calling error rate when evaluated at the mean error rate of 13.3%. Restricting the sample to borderline pitches increases the magnitude of the hot-weather effect on accuracy to over a percentage point. My results indicate that very hot temperatures have a nontrivial, negative effect on the labor supply quality of a highly trained and highly skilled workforce in an important, high-revenue, and high-stakes industry, and suggest that protecting workers from daily variation in temperature can improve labor productivity.